Measurement of tracheobronchial clearance after sauna in subjects with chronic bronchitis. - van Hengstum, M (1991)
The effect of sauna on tracheobronchial clearance was studied in five male patients with chronic bronchitis by a radioaerosol technique. No enhancement of tracheobronchial clearance could be detected.